Arrhythmogenic Right Ventricular Cardiomyopathy-Associated Desmosomal Variants Are Rarely De Novo: Segregation and Haplotype Analysis of a Multinational Cohort. (August 2019) - van Lint, Freyja H.M.; Murray, Brittney; Tichnell, Crystal; Zwart, Rob; Amat, Nuria; Lekanne Deprez, Ronald H.; Dittmann, Sven; Stallmeyer, Birgit; Calkins, Hugh; van der Smagt, Jasper J.; van den Wijngaard, Arthur; Dooijes, Dennis; et al.
Abstract : Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is associated with pathogenic/likely pathogenic (P/LP) variants in genes encoding the cardiac desmosomal proteins. Origin of these variants, including de novo mutation rate and extent of founder versus recurrent variants has implications for variant adjudication and clinical care, yet this has never been systematically investigated. Methods: We identified arrhythmogenic right ventricular cardiomyopathy probands who met 2010 Task Force Criteria and had undergone genotyping that included sequencing of the desmosomal genes ( PKP2, DSP, DSG2, DSC2, and JUP ) from 3 arrhythmogenic right ventricular cardiomyopathy registries in America and Europe. We classified the desmosomal variants, defined the contribution of unique versus nonunique (ie, not family-specific) P/LP variants, and identified the frequency and characteristics of de novo variants. Next, we haplotyped nonunique variants to determine how often they likely represent a single mutation event in a common ancestor (implied by shared haplotypes) versus multiple mutation events at the same genetic location. Results: Of 501 arrhythmogenic right ventricular cardiomyopathy probands, 322 (64.3%) carried 327 desmosomal P/LP variants. Most variants (n=247, 75.6%, in 245 patients) were identified in more than one proband and, therefore, considered nonunique. For 212/327 variants (64.8%) genetic cascade screening was performed extensively enough to identify the parental origin of the P/LP variant. Only 3 variants were de novo, 2 of which were whole gene deletions. For 24 nonunique P/LP PKP2 variants, haplotyping was conducted in 183 available families. For all 24 variants, multiple seemingly unrelated families sharing identical haplotypes were identified, suggesting that these variants originate from common founders. Conclusions: Most desmosomal P/LP variants are inherited, nonunique, and originate from ancient founders. Two of 3 de novo variants were large deletions. These observations inform genetic testing, cascade screening, and variant adjudication. Abstract : Supplemental Digital Content is available in the text.